DETERMINASI PRESTASI BELAJAR SISWA PADA SEKOLAH BERBASIS PESANTREN - Ahmad Fuad Hasyim (Wahana Islamika: Jurnal Studi Keislaman, 2022)
The learning achievement of students majoring in fashion at SMK Syubbanul Wathon has been satisfactory; this is evidenced by the semester scores of students majoring in fashion having reached the KKM (Minimum Completeness Criteria); there are only a few students who still get scores below the KKM (Minimum Completeness Criteria). This study aimed to determine the variables that affect student achievement. Student achievement can be influenced by classroom management and teacher professionalism. In this study, quantitative research methods were used using primary data. The sample used in this study was 133 randomly selected. The data analysis used multiple linear regression. The results showed that all the independent variables simultaneously significantly affected the learning achievement variable. Partially, all independent variables have a significant effect on student achievement.